Interfacial Interactions in Calcium Carbonate Materials in the Context of Biomedical Applications - Myszka, Barbara (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

Mechanical improvement of calcium carbonate cements by: In situ HEMA polymerization during hardening - Myszka, Barbara; Hurle, Katrin; Zheng, Kai; Wolf, Stephan; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2019)
Calcium carbonate cements are a promising alternative for calcium phosphate cements. Due to the higher solubility of calcium carbonate compared to apatite, it is expected to have an improved biodegradation rate; a clear advantage for prospective biomedical applications in a clinical context. As of yet, the poor mechanical performance of calcium carbonate cements precludes their exploitation as a bioceramic. Herein, we report a mechanically enhanced calcium carbonate cement, formulated of vaterite and magnesium-doped amorphous calcium carbonate, which was strengthened by in situ polymerization of incorporated 2-hydroxyethylmethacrylate (HEMA) during setting in simulated body fluid (SBF). This approach allowed us to generate a pronouncedly strengthened polymer-ceramic composite whose mechanical properties can be tuned by the monomer fraction. Varying cement compositions were characterized with respect to their mechanical performance, morphology, and quantitative phase composition. HEMA polymer reinforcement strengthened the calcium carbonate cement distinctly in four-point bending test while, in stark contrast, the brittleness of the polymer-free cement simply made such tests impossible. Our results demonstrate that the chosen polymer-enforcement strategy is an efficient and straightforward approach and allows for tuning the mechanical properties of an otherwise brittle and thus unusable calcium carbonate cement towards biomedical application.
CRIS-Team Scopus Importer:2019-06-25

Phase-specific bioactivity and altered Ostwald ripening pathways of calcium carbonate polymorphs in simulated body fluid - Myszka, Barbara; Schüßler, Martina; Hurle, Katrin; Demmert, Benedikt; Detsch, Rainer; Boccaccini, Aldo R.; Wolf, Stephan (RSC Advances, 2019)
Calcium carbonate is an abundant biomineral, and already archeological records demonstrate its bioactivity and applicability for osseo-integrative implants. Its solubility, which is generally higher than those of calcium phosphates, depends on its polymorph turning calcium carbonate into a promising biomaterial with tunable bioresorption rate. However, the phase-dependent bioactivity of calcium carbonate, i.e., its osteoconductivity, is still insufficiently characterized. In this study, we address this issue by monitoring the behavior of the four most important calcium carbonate phases, i.e., calcite, aragonite, vaterite, and amorphous calcium carbonate, in simulated body fluid solution at 37 °C. Our results demonstrate that the thermodynamically stable calcite phase is essentially inert. In contrast, the metastable phases aragonite and vaterite are bioactive, thus promoting the formation of calcium phosphate. Amorphous calcium carbonate (ACC) shows prominent bioactivity accompanied by pronounced redissolution processes. Mg-stabilized ACC was additionally tested since its increased stability eases formulation and handling in future applications. It is highly bioactive and, moreover, the additional release of Mg promotes cell viability. Overall, our results demonstrate that bioactivity of calcium carbonate is phase-dependent, allowing tailored response and bioactivity of future calcareous biomaterials. Our results also reveal that phosphate ions strongly interfere with Ostwald-Lussac step ripening of calcium carbonate, kinetically stabilizing metastable polymorphs such as vaterite and aragonite; this is a distinctive feature of the calcium carbonate mineral system which clearly has to be considered in future applications of calcium carbonate as a bioceramic.
CRIS-Team Scopus Importer:2019-07-09

Setting behavior and bioactivity assessment of calcium carbonate cements - Rodríguez-Sánchez, Jesús; Myszka, Barbara; Boccaccini, Aldo R.; Dysthe, Dag Kristian (Journal of the American Ceramic Society, 2019)
Calcium carbonate cements have emerged in the last few years as an attractive candidate for biomedical applications. They can be easily prepared by mixing water with two metastable calcium carbonate phases––amorphous calcium carbonate (ACC) and vaterite––which (re)crystallize into calcite during setting reaction. The transformation kinetics (and therefore the final surface cement composition) strongly depends on the initial mixture design and is controlled by the dissolution of ACC, whereas calcite nucleation typically controls their recrystallization in fluid batch experiments. Novel compositions are presented in this paper by incorporating organic molecules as a proxy to test their capability to carry on other biomolecules like proteins or antibiotics. The hardened samples are microporous and show excellent bioactivity rates, although their mechanical properties still remain poor. However, this would not be a handicap for in-vivo applications such as bone filling, especially in low mechanical stress locations.
CRIS-Team Scopus Importer:2019-09-17
Keywords: (re)crystallization kinetics; apatite-like precipitation; bioactivity; CaCO; compressive strength

Shape Matters: Crystal Morphology and Surface Topography Alter Bioactivity of Bioceramics in Simulated Body Fluid - Myszka, Barbara; Schodder, Philipp; Leupold, Simon; Barr, Maissa; Hurle, Katrin; Schüßler, Martina; Demmert, Benedikt; Biggemann, Jonas; Fey, Tobias; Boccaccini, Aldo R.; Wolf, Stephan (Advanced Engineering Materials, 2020)
For bioactive biomaterials such as bioceramics and bioglass, it is generally accepted that, apart from acting as heterogeneous nucleators, it is their solubility and the resulting release of relevant ions such as calcium or basic anions which mainly governs the biomaterial's bioactivity. This contribution reveals that this bioactivity, as assessed by simulated body fluid (SBF), can also be considerably modified by the bioceramic's morphology, i.e., bioactivity is also governed by microstructure and surface morphology. When crystals are forced to adopt out-of-equilibrium crystal habit, this simple change in morphology converts an essentially bioinert material, here calcite, into a bioceramic which shows bioactivity in SBF. On larger length scales, already simple morphological changes, such as scratches, can have inverse effects. Limited mass transport into grooves and pits on a bioceramic surface can lead to local ion depletion which, in turn, causes reduced bioactivity of bioceramics which, otherwise, show distinct bioactivity in SBF. This contribution emblematically illustrates the unforeseen importance of even minor morphology changes on different length scales when assessing and designing a biomaterial's bioactivity through SBF assays.
CRIS-Team Scopus Importer:2020-06-05
Keywords: bioactivity; bioceramics; biomaterials; calcium carbonate; crystallization

Sonosynthesis of Vaterite-Type Calcium Carbonate - Juhasz-Bortuzzo, Judith; Myszka, Barbara; Silva, Raquel; Boccaccini, Aldo R. (Crystal Growth & Design, 2017)